Identification and characterization of three novel mutations in the CASQ1 gene in four patients with tubular aggregate myopathy. Issue 12 (26th September 2017) - Barone, Virginia; Del Re, Valeria; Gamberucci, Alessandra; Polverino, Valentina; Galli, Lucia; Rossi, Daniela; Costanzi, Elisa; Toniolo, Luana; Berti, Gianna; Malandrini, Alessandro; Ricci, Giulia; Siciliano, Gabriele; et al.
Abstract: Here, we report the identification of three novel missense mutations in the calsequestrin‐1 ( CASQ1 ) gene in four patients with tubular aggregate myopathy. These CASQ1 mutations affect conserved amino acids in position 44 (p.(Asp44Asn)), 103 (p.(Gly103Asp)), and 385 (p.(Ile385Thr)). Functional studies, based on turbidity and dynamic light scattering measurements at increasing Ca 2+ concentrations, showed a reduced Ca 2+ ‐dependent aggregation for the CASQ1 protein containing p.Asp44Asn and p.Gly103Asp mutations and a slight increase in Ca 2+ ‐dependent aggregation for the p.Ile385Thr. Accordingly, limited trypsin proteolysis assay showed that p.Asp44Asn and p.Gly103Asp were more susceptible to trypsin cleavage in the presence of Ca 2+ in comparison with WT and p.Ile385Thr. Analysis of single muscle fibers of a patient carrying the p.Gly103Asp mutation showed a significant reduction in response to caffeine stimulation, compared with normal control fibers. Expression of CASQ1 mutations in eukaryotic cells revealed a reduced ability of all these CASQ1 mutants to store Ca 2+ and a reduced inhibitory effect of p.Ile385Thr and p.Asp44Asn on store operated Ca 2+ entry. These results widen the spectrum of skeletal muscle diseases associated with CASQ1 and indicate that these mutations affect properties critical for correct Ca 2+ handling in skeletal muscle fibers. Abstract : CASQ1 is a Ca 2+ ‐binding protein present in the sarcoplasmic reticulum of skeletal muscle fibers where its function is to store and make available the large amounts of Ca 2+ necessary for activation of muscle contraction. Mutations in CASQ1 have been found in patients with Tubular Aggregate Myopathy. These mutations appear to localize at site of interactions between CASQ1 monomers and dimers. Alterations of these interactions are proposed to reduce the ability of CASQ1 to assemble in large polymers with increased Ca 2+ binding ability.